Biomedical Applications: Ultrasound‐Induced Wireless Energy Harvesting for Potential Retinal Electrical Stimulation Application (Adv. Funct. Mater. 33/2019). (13th August 2019) - Jiang, Laiming; Yang, Yang; Chen, Ruimin; Lu, Gengxi; Li, Runze; Xing, Jie; Shung, K. Kirk; Humayun, Mark S.; Zhu, Jianguo; Chen, Yong; Zhou, Qifa
Abstract : In article number1902522, Yang Yang, Jianguo Zhu, Yong Chen, Qifa Zhou, and co‐workers demonstrate a potential retinal electrical stimulation strategy using ultrasound‐driven wireless energy harvesting technology through a millmeter‐scale lead‐free ultrasonic energy harvesting device. The as‐developed device is flexible and can be attached on a complex surface and be driven by ultrasound to produce adjustable electrical outputs.